2004
DOI: 10.1038/sj.cdd.4401490
|View full text |Cite
|
Sign up to set email alerts
|

EDAG regulates the proliferation and differentiation of hematopoietic cells and resists cell apoptosis through the activation of nuclear factor-κB

Abstract: Erythroid differentiation-associated gene (EDAG) is considered to be a human hematopoiesis-specific gene. Here, we reported that downregulation of EDAG protein in K562 cells resulted in inhibition of growth and colony formation, and enhancement of sensitivity to erythroid differentiation induced by hemin. Overexpression of EDAG in HL-60 cells significantly blocked the expression of the monocyte/ macrophage differentiation marker CD11b after pentahydroxytiglia myristate acetate induction. Moreover, overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 29 publications
2
88
0
Order By: Relevance
“…promoting genes [1], it has been proposed that cell fate following growth factor withdrawal is determined by the ability to maintain NF-κB activity [31][32][33]. In line with this notion, previous studies observed a large decrease in NF-κB activity before the propagation of apoptosis when Ba/F3 cells were deprived of IL-3 [30].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…promoting genes [1], it has been proposed that cell fate following growth factor withdrawal is determined by the ability to maintain NF-κB activity [31][32][33]. In line with this notion, previous studies observed a large decrease in NF-κB activity before the propagation of apoptosis when Ba/F3 cells were deprived of IL-3 [30].…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, Ba/F3 cells become committed to apoptosis when deprived of IL-3, and hence multiple signaling pathways downstream of IL-3 have been proposed to prevent apoptosis [29]. For instance, the constitutive activation of NF-κB in the presence of IL-3 is required for the survival of Ba/F3 cells [30][31][32]. As NF-κB activation is known to protect cells against apoptosis through the transcriptional upregulation of survival- At the indicated time points, cell death was assessed by cytofluorometric analysis of PI uptake.…”
Section: Discussionmentioning
confidence: 99%
“…2 EDAG is highly expressed in acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) and has been demonstrated to be involved in erythroleukemia differentiation, survival and apoptosis and cell transformation of NIH3T3 cells. 4,5 ALL these studies suggest that overexpression of EDAG in acute leukemia may play an important role in leukemogensis. More recently, assocaition of overexpression of EDAG and no remission in de novo AML has been reported: this result suggests that EDAG may play a modulator role in AML and could be a new target in the treatment of AML.…”
Section: Introductionmentioning
confidence: 92%
“…Overexpression of EDAG in NIH3T3 cells causes cell transforming and tumor forming in nude mice. 2 Furthermore, EDAG gene maps to chromosome 9q22, which contains a cluster of leukemic breakpoints and genes important for leukemogenesis. 1 However, its clinical significance and function in leukemogenesis is still unclear.…”
Section: High Expression Of Edag and Its Significance In Amlmentioning
confidence: 99%
“…This accords with the reports of others. 2 In this study, we also studied the effect of knockdown of EDAG expression by RNAi on the expression of some genes related to cell cycle, apoptosis or hematopoiesis, including cyclin A1, cyclin D1, cyclin D2, cyclin E, cdk2, p21, SCL/tal-1, GATA-2, c-myb, c-Myc, Bcl-2, NF-kB, and Notch1 (Figure 2). We found that p21 expression was increased in the EDAG knockdown K562 cells.…”
Section: High Expression Of Edag and Its Significance In Amlmentioning
confidence: 99%